Development of distance learning courses on statistics - Janilionis, Vytautas (Lietuvos matematikos rinkinys, 2000)
The problems of the development of web-based distance learning (DL) courses on Statistics are analysed in the paper. DL methods and technologies for the development and provision of DL courses on Statistics are reviewed. The Internet resources (electronic books, video, simulation, animation, text, interactive experiments, software package which provides routines for statistical analysis via the WWW) and application of DL course development software are analysed. The. experience of the developer of the first Lithuanian web-based course on Statistics ``Statistics and Data Analysis Software'' is presented in the paper.